The clinical impact of testing for biomarkers in gastric cancer patients: a real‐world cohort. Issue 6 (21st February 2023) - van der Sluis, Karen; van Sandick, Johanna W; van Dieren, Jolanda M; Vollebergh, Marieke A; Grootscholten, Cecile; van den Berg, José G; Snaebjornsson, Petur; Hartemink, Koen J; Veenhof, Alexander A F A; Chalabi, Myriam; Kodach, Liudmila L
Abstract : Background and aims: In gastric cancer (GC), HER2 was the first biomarker for guided therapy registered for clinical use. Considering the recent approvals of immune check‐point blockade (ICB) in gastro‐oesophageal cancers, testing for mismatch repair deficiency (dMMR), Epstein–Barr virus (EBV) and PD‐L1 combined positive score (CPS) is becoming increasingly important. Here we describe a real‐world cohort on biomarker assessment in GC patients. Methods: Patients diagnosed with GC between 2017 and 2021 were included. Biomarker results were retrieved from electronic patient files. PD‐L1 CPS was determined retrospectively on dMMR and EBV‐positive (EBV+) tumours. Data on genomic sequencing were analysed separately. Results: Of 363 patients identified, 45% had metastatic disease. In 335 patients (92%) at least one biomarker was tested. The prevalence of HER2+, dMMR and EBV+ tumours was 10% (32 of 319), 7% (20 of 294) and 1% (three of 235), respectively. Of the dMMR and EBV+ tumours, 95% had a PD‐L1 CPS ≥ 5. Therapeutic strategy was adjusted in 31 of 55 patients and consisted of anti‐HER2 therapies as well as ICB in clinical trials. Genomic alterations were found in 44 of 60 tested patients. TP53 (73%) and PIK3CA (20%) mutations were most common, followed by KRAS mutations (11%) and amplifications (11%). Conclusions: In this real‐world cohort, testing for HER2, dMMR and EBV status affected treatment decisions in 56% of the patients. Although most dMMR and EBV+ tumours had a PD‐L1 CPS ≥ 5, not all patients with a high probability of treatment response are identified. Based on these results, a stepwise diagnostic strategy is proposed. Abstract : In this real‐world cohort, testing for HER2, dMMR and EBV status affected treatment decisions in 56% of the patients. Although most dMMR and EBV+ tumors had a PD‐L1 CPS≥5, not all patients with a high probability of response are identified. Based on these results, we propose a stepwise diagnostic strategy.